PAT applied in biopharmaceutical process development and manufacturing : an enabling tool for quality-by-design - Undey, Cenk (Biotechnology and bioprocessing series ;, 2012)
"This book summarizes the state of the art in process analytical technologies applied to various aspects of biopharmaceutical process development and manufacturing. The text summarizes regulatory perspectives, FDA/EMEA guidelines, and new expectations. In addition, it explores new technology, especially in the area of real-time monitoring for end-point control as well as new sensor and analytical technologies. It details established and emerging measurement technologies, including future needs and challenges that require further research. The authors also present successful industrial-scale deployment case studies and strategies from the biopharmaceutical industry and discuss future trends."